Penulisan Modul Ajar/Modul Pembelajaran bagi Guru-guru SMK Tarbiyatul Ullum Sumur Songo Magetan - Makhmudiyah, Soeparno; Wiyono, Agus; Alidrus, Sammy (Mejuajua: Jurnal Pengabdian pada Masyarakat, 2025)
The development of teaching materials is one way to improve the quality of learning in schools. The development of teaching materials in the form of modules is currently very important because the implementation of modules can condition learning activities more planned, independent, complete, and with clear results. Thus, educators can help schools achieve high standards of learning. The workshop program for the preparation of teaching modules/learning modules for teachers is very important and urgent. This is in accordance with the condition of the regulatory problems that apply to teachers related to the enactment of the Regulation of the Minister of State on the Empowerment of the State Apparatus and Bureaucratic Reform Number 16 of 2009 concerning Teachers' Functional Positions and Credit Scores. This problem also applies and has an impact on teachers of SMK Tarbiyatul Ullum Sumorsongo Magetan who still do not have written works in the form of teaching modules/learning modules. Therefore, the PKM FT Unesa team provides workshops on writing textbooks and scientific articles at SMK Tarbiyatul Ullum Sumorsongo Magetan with the aim of 1) introducing and equipping educators about teaching modules, and 2) to help educators make teaching modules. The implementation methods used in this activity are lectures, practices and discussions.